HIV-1-exposed seronegative individuals show alteration in TLR expression and pro-inflammatory cytokine production ex vivo: An innate immune quiescence status? (2023)
Pattern recognition receptors (PRRs) are involved in direct recognition of viruses, promoting cellular activation and the production of pro-inflammatory cytokines. However, despite the reduced systemic immune activation described in HIV-1-exposed seronegatives (HESNs), few studies have focused on determining the relationship between PRR expression and cytokine production. We have aimed here to evaluate the expression level of PRRs and cytokines in HESNs, HIV-1 patients and healthy donors. Basal PRR expression levels in PBMCs, dendritic cells (DCs) and monocytes, and plasma cytokine levels as well as the PRR ligand-induced cytokine productions were determined by flow cytometry, qPCR and ELISA. Higher TLR2/4 expression in DCs and monocytes from HESNs was observed. Nevertheless, TLR4/8, NOD2 and RIG-I mRNA levels were lower in PBMCs from HESNs than HIV-1-infected patients. Comparable IL-1ß, IL-18 and TNF-a mRNA levels were observed among the groups examined; however, at the protein level, production of IL-1ß, IL-6 and IL-10 was significantly lower in plasma from HESNs than from HIV-1-infected patients. Our results suggest that exposure to HIV-1 without infection could be associated with reduced basal pro-inflammatory responses. Further studies are required to define the cell subsets responsible for these differences and the role of PRRs on protection against HIV-1 infection. © 2015, Springer Science+Business Media New York.